(untitled) (Philippines, 1994)
Fish nutrition research in Asia is the first book to provide comprehensive information on nutrition as a means to improve fish health and defend against infection.
Keywords: Fish,Fish culture,Cá,Chăn nuôi cá; Feeding,Chăn nuôi